As representações sociais sobre o ensino de psicologia da educação e suas contribuições para a formação do educador - RODRIGUES, Sônia Eli Cabral (2006)
This works intends to study the social representaions os licentiaship courses of Universidade Federal do Pará about the teach of Psychology of Education. This study is based in the theorecal-methodological reference of social representations (moscovician reference os Social Psychology) to analyse the prodution of meanings, that are partake by students, about the teach of this discipline at UFPA (campus of Belém). By support of this theory, we begin thinking that knowledg are produces and elaborated, in the common sense, in the division social groups and orient thinkings, feelings and actis of these groups. Seventh students, that made the dispcipline, of six licenciateaship courses of UFPA Belém, participated in this study. We used in the basis collection two differents: the questionaire with mixture questions and the technic of focus group. The basis passed by a quantitative and qualitative treatment based in the statical analysis ad content analysis of Bardin (1977), what possibilited us to verify that social representations fo students, about the teach of Psychology Education, are in common meaning of this way: the students show that discipline has add with psychological knowledges (psychological theories, learning and development process) that can be applied to pratice of education; they consider teach of Psychology Positive, but they feel the deficiency of articulation between the contents od discipline, the educational reality, the courses specicific contents and the realtion between pedagoci theory and pratice. These basis about the teach of Psychology shows that discipline can contribute much more to formation of teachers, articulating of integrate way the dimensions of learning-tech process that are the content os Psychlogy of Education, in the way of pedagogic work and in the objective of to form teachers, These social representations of etudents are important because gives support to reflections, debates and propositions about the teach of Psychology of Education in the licenciatechip courses of UFPA.